LOCAL CHANGE IN THE STRESS STATE IN ROCK SAMPLES BEFORE DESTRUCTION ACCORDING TO THE LODE–NADAI COEFFICIENT - Lementueva, R.A.; Rebetsky, Yu.L.; Bubnova, N.Ya; Treusov, A.V. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2024)
In this paper, the relationship of the Lode–Nadai coefficient, which determines the shape of the stress ellipsoid, with the nature of brittle fracture in sandstone, pyrophyllite and dolomite samples for a rigid loading machine is investigated. The measurement of the inhomogeneous deformation field in the samples and the observation of the internal fracture process were performed using strain gauges and acoustic sensors. It is shown that the formation of the main crack is preceded by the evolution of local deformations in the sample, recorded by the strain gauge method. Special processing of strain gauge data, taking into account the free lateral surface of the samples, made it possible to calculate the principle deformations and three invariants of the strain tensor: maximum shear deformation, volume change deformation and the Lode–Nadai coefficient. It has been established that at the final stage of deformation, when a main crack is formed in local sections of the sample, the axes of the principal deformations are reindexed, which is expressed in the achievement of the maximum values of +1 and -1 by the Lode–Nadai coefficient. A comparison with field observations was made.